Optimal crop choice: farmer adaptation to climate change - Leopoldo E. Soto Arriagada (Claremont McKenna College, Department of Economics, 2005)
I use a Mixed Logit model and the most detailed agricultural data publicly available to show how farmers employ land allocation as an adaptation mechanism in the face of a changing environment. The driving forces behind the farmer's land-use choice are differences between the crops available for cultivation as well as the soil, climate, and observable and unobservable (to the econometrician) characteristics of the farm. I present a measure of the effects of climate change on agricultural land value based on a structural model of farmer behavior and a mix of data at the plot, county, state and national levels. Results from most previous research are based on county-level data. The improved resolution of the data used in this paper allows us to test the validity of assumptions made in earlier work. Moreover, results show that substitution across crops depends directly on differences in climate for each plot.
Keywords: Q1; Q2; C5; 330; Climate Change; Adaptation Costs; Land Rents; Mixed Logit